(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Low height-for-age (stunting) is a state of chronic undernutrition in children and adolescents. Studies reported that India has very high prevalence of stunting in children, particularly from rural and tribal communities. Objective of the present study was to record prevalence of stunting in 6 to 18 year-old boys and girls from two tribal communities (Limbu and Mech) in Darjeeling and Alipurduar districts of West Bengal, India. The study also aimed to compare height-for-age of the participants with standard growth reference curves. Methods: In this cross-sectional study, the sample comprises 1523 individuals of both sexes from Limbu (377 boys, 379 girls) and Mech (365 boys, 402 girls) communities. Height data was normalized using LMS. Results: Overall frequency of stunting among 6 to 18 year-old boys (33%) and girls (34.7%) was remarkably high. Prevalence of stunting was higher in Limbu boys (43.5%) and girls (44.6%) than their age-peers from Mech community (boys 22.2%, girls 25.4%). Height data after normalization, shows that all centile curves of height of Limbu and Mech boys and girls are consistently below the standard height-for-age reference curves of the WHO. Limbu and Mech children appear to be taller with respect to their median (50th percentile) height when compared with the median height of children in the dataset of Indian Council of Medical Research. Conclusion: High frequency stunting in Mech and limbu children was recorded and situation of girls was worse. There was a tendency of decline in prevalence of stunting with advancement of age among children.